A giant step for Malaysia towards Vision 2020 - Abd Razak, Dzulkifli (2007)
Hari Raya Aidilfitri has always been a special occasion for all Malaysians. This year is even more the case in view of the 50th anniversary of independence, epitomised by the launching of the first Malaysian into space. The word "victory" would most appropriately describe these major events. Hari Raya Aidilfitri, for instance, is a big "victory" for those who have completed a monthlong fast during the holy month of Ramadan. They rightly deserve to celebrate Hari Raya as a reward for their victorious struggle against worldly wants and demands.